Republic of Estonia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2009)
This paper presents key findings of the Financial System Stability Assessment of the Republic of Estonia. The Estonian financial sector is highly concentrated and foreign owned. Financial indicators suggest a sound banking sector, and show particular strength in asset quality and earnings. The paper reveals that the Estonian banking sector has significant vulnerabilities from its real-estate lending. The rapid expansion of the banking sector has been funded, to a large extent, by short-term foreign borrowing from parent banks, making Estonia vulnerable to a disruption in international financial markets.